2019
DOI: 10.1039/c8nr08014c
|View full text |Cite
|
Sign up to set email alerts
|

Stable, color-tunable 2D SCN-based perovskites: revealing the critical influence of an asymmetric pseudo-halide on constituent ions

Abstract: It is revealed that the linear SCN− anion dictates critical restriction on the constituent ions of its derived 2D (PbX4(SCN)2) framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 43 publications
2
36
0
Order By: Relevance
“…The characteristic PL lifetimes of CH 3 NH 3 PbI 3 at 773 nm are 1.9 ns (56%) and 7.8 ns (44%). These results [19,45].…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…The characteristic PL lifetimes of CH 3 NH 3 PbI 3 at 773 nm are 1.9 ns (56%) and 7.8 ns (44%). These results [19,45].…”
Section: Resultsmentioning
confidence: 63%
“…This result also confirms that the emission at 600 nm is due to singlet exciton while the emission at the main peak (757 nm) is due to triplet excitons. The observation of very short PL emission lifetime of 600 nm peak and long lifetime PL emission lifetime of 757 nm peak indicates that the recombination in (CH 3 NH 3 ) 2 Pb(SCN) 2 I 2 is dominated by excitonic recombination, and the 757 nm peak is associated with triplet excitons [19]. It has also been reported that this peak may be related to triplet excitons or defective states [19].…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Such ε r is high compared to those (ε r = 3.3–15.1) of perovskite crystals with long‐chain organic barriers. [ 33–35 ] Such high dielectric constant would reduce the exciton binding energy E b due to the inverse square relationship. [ 36 ] We measured E b of 2D Cs 2 Pb(SCN) 2 Br 2 single crystal using temperature‐dependent PL (temp‐PL) (Figure S13a, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%